The Relationship between Identity Exploration and Career Maturity with Quarter-Life Crisis among Final-Year Students at Muhammadiyah University of Surabaya - Intan Fauzi; Rinanti Resmadewi; Iffah Rosyiana (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to examine the relationship between identity exploration and career maturity with quarter-life crisis among final-year students at Muhammadiyah University of Surabaya. The study used a sample of 149 final-year students from Muhammadiyah University of Surabaya, selected through purposive sampling. The scales used in this research were constructed based on each respective theory. The hypothesis testing employed in this study was multiple linear regression analysis to assess the relationship between identity exploration, career maturity, and quarter-life crisis. The results showed that there is a significant relationship between identity exploration and career maturity when correlated together with quarter-life crisis. The variables of identity exploration and career maturity collectively contributed 37.4% (R-square = 0.374) to the quarter-life crisis. Based on this, it can be concluded that there is a relationship between identity exploration and career maturity with quarter-life crisis.